Investigating Virtual Learning on Students Learning Outcomes in Urban and Rural Areas - Hariyati, Nunuk; Wagino, Wagino; Mudjito, Mudjito (Dinamika Pendidikan, 2021)
This study aims to investigate the implementation of virtual learning on students’ learning outcomes mediated by motivation and to compare its effectiveness between urban and rural areas. This study employed quantitative design, involved 362 students of Faculty of Education in UNESA. To determine the sample, it employed Solvin’s formula. The data were collected by using three instruments, specifically Virtual Learning Effectiveness, Learning Outcomes, and Motivation. To see the difference of virtual learning on learning outcomes mediated by motivation based on student’s location, path analysis was performed twice by separating the data into two kinds of groups. The first group contains student’s data that lived in an urban area. The second group contains student’s data that lived in a rural area. The findings of this research confirm that the virtual learning is effective to improve students’ learning outcomes which was mediated by motivation. In addition, it was found that the motivation of students from urban areas is higher than those from rural areas. It suggests that the native location of students influences their motivation.